Surface engineering for safer walking environments: Optimising floor coatings for enhanced slip resistance - In-Ju Kim (Results in Engineering)
Slip-related falls pose a significant safety risk in residential, commercial, and industrial settings, often resulting in severe injuries and considerable economic costs. This study systematically evaluates the slip resistance performance of four floor coating agents—epoxy, polymer, acrylic, and acid-based etchant—applied to ceramic tiles under different environmental conditions (arid, damp, and foamy). Dynamic friction tests and surface roughness measurements were conducted before and after coating application to investigate the relationship between surface texture and slip resistance. Results show that the acid-based etchant coating substantially improved slip resistance on arid surfaces, with up to a 95 % increase in surface roughness. Epoxy coatings demonstrated superior performance under damp conditions, achieving up to a 45 % enhancement in dynamic friction, making them suitable for areas with frequent water exposure. Acrylic polymer coatings showed the most consistent performance across damp and foamy conditions, highlighting their versatility in high-risk settings such as industrial kitchens. In contrast, acrylic coatings exhibited moderate improvements in slip resistance under arid conditions but performed poorly in foamy environments. These findings emphasise the importance of selecting floor coatings based on specific environmental conditions to optimise pedestrian safety. Practical recommendations are offered for industries seeking to minimise slip-related fall risks through informed coating choices. The study also outlines future research directions, including assessing the long-term durability of coatings and exploring emerging technologies, such as nanocoatings, to further enhance slip resistance in complex environments. These insights aim to contribute to safer built environments by mitigating slip hazards across diverse settings.